Respon Petani Terhadap Penyuluhan Pekarangan Pangan Lestari (P2L) Kelompok Tani Pusaka I, Desa Babakan Kabupaten Purwakarta - Siti Mariyani; Kuswarini Sulandjari; Puji Raihani (Jurnal Agrimanex: Agribusiness, Rural Management, and Development Extension, 2022)
Farmer groups Pusaka 1 Babakan Village, Purwakarta Regency is one of the farmer groups who have received P2L assistance since 2020 but there are still some obstacles in implementing the P2L program, including the knowledge of members in cultivation activities in the yard of the house. Efforts to increase farmers' knowledge is through counseling by BPP Wanayasa. This study aims to determine the response of farmers from the Pekarangan Pangan Lestari (P2L) program to the extension activities carried out by BPP Wanayasa by assessing the knowledge, attitudes and skills of farmer group members. The research method is a survey using quantitative data supported by qualitative data. Respondents were selected by simple random sampling as many as 15 farmers. The research object was chosen purposively, namely the Farmer groups Pusaka 1 Babakan village because it received P2L assistance. The results showed that the knowledge of farmers after counseling in the form of making compost increased to 73.3%, pest control methods became 100%, knowing plants that have a value high economic value to 93.3% and good land management to 86.7%. The attitude of farmers to extension activities gave a very good response, namely 80%. Farmers' skills in marketing aspects of crop yields and the added value of crop yields did not change too much before and after the extension was held, so it was concluded that farmers gave a very good response to extension and there was an increase in knowledge. However, the extension has not completely changed the skills of members of the heritage farmer group 1 program of the Sustainable Food Garden (P2L). Kata kunci: farmer groups, food, counseling, response, yard.